2013
DOI: 10.1007/978-3-642-40480-1_55
|View full text |Cite
|
Sign up to set email alerts
|

Using Video Prototypes for Evaluating Design Concepts with Users: A Comparison to Usability Testing

Abstract: Abstract. We present an exploratory study that compared user feedback obtained from evaluating a mobile application versus a reverse engineered video prototype of this same application. The comparison included qualitative and quantitative data analysis. Questionnaire responses regarding user acceptance (UTAUT [8]) and the overall user experience (AttrakDiff [4]) showed no differences. Qualitative analysis of the comments by potential users yielded similar results. Some differences regarding comments pertaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Within this framework, we integrated 3 participatory activities deemed specifically effective for people with LHL. These were (1) “co-constructing stories” [ 43 ], (2) “experience prototype exhibition” [ 44 ], and (3) “video prototype evaluation” [ 45 ]. These activities were specifically selected as they would allow to effectively engage with the target group and understand their perspective.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this framework, we integrated 3 participatory activities deemed specifically effective for people with LHL. These were (1) “co-constructing stories” [ 43 ], (2) “experience prototype exhibition” [ 44 ], and (3) “video prototype evaluation” [ 45 ]. These activities were specifically selected as they would allow to effectively engage with the target group and understand their perspective.…”
Section: Methodsmentioning
confidence: 99%
“…A combination of paper and video prototypes would be more effective in communicating the concept toward people with LHL than paper-based prototypes alone. [ 45 , 49 ]. Videos have proven to be an effective tool in other intervention research and design efforts for asthma patients with LHL [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using a video prototype allows us to discuss design ideas beyond the screen and focus on the use of generative AI in reminiscence contexts. In addition, the video prototype could present design ideas vividly and efficiently and support participatory design [51,94]. Specifically, the video prototype demonstrates how a virtual DJ (AI-DJ) guides listeners to recall and share their memories while listening to nostalgic songs.…”
Section: Workhop I: Understanding Older Adultsmentioning
confidence: 99%
“…Indeed, studies assessing the ecological validity of video-based study designs have shown the results to closely mirror reality, particularly when assessing user acceptance and usability considerations. The main difference between video and usage-based studies is that users may not always be able to fully assess restrictions posed by the context where the interaction takes place [35]. Video prototypes also offer other benefits as they help in obtaining a higher number of participants and responses from a variety of regions, where users opinion and adoption of multidevice systems can differ significantly, and as they help reproducing and replicating the study at different locations.…”
Section: Experiments Designmentioning
confidence: 99%